2017
DOI: 10.1637/11609-021317-regr
|View full text |Cite
|
Sign up to set email alerts
|

Presence ofAvibacterium paragallinarumand Histopathologic Lesions Corresponds with Clinical Signs in a Co-infection Model withGallibacterium anatis

Abstract: Recently we demonstrated that co-infection with Avibacterium paragallinarum and Gallibacterium anatis leads to increased severity of clinical signs of infectious coryza in birds. The present study examined the interaction of these two pathogens in chickens by evaluation of histologic lesions in sinus infraorbitalis and nasal turbinates, applying a defined scoring scheme ranging from 0 to 3. Furthermore, for the first time, an in situ hybridization (ISH) technique was applied to detect A. paragallinarum in tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…The OMVs of Acinetobacter baumannii interact with macrophages to induce the secretion of both pro‐ and anti-inflammatory cytokines, leading to uncontrolled chronic inflammation ( Ahmad et al, 2019 ). It has been suggested that A. paragallinarum may have an immunomodulatory potential that influences host defense and inflammation ( Paudel et al, 2017 ). Our results suggest that it is possible that the OMVs of A. paragallinarum involved in such influence on host responses.…”
Section: Discussionmentioning
confidence: 99%
“…The OMVs of Acinetobacter baumannii interact with macrophages to induce the secretion of both pro‐ and anti-inflammatory cytokines, leading to uncontrolled chronic inflammation ( Ahmad et al, 2019 ). It has been suggested that A. paragallinarum may have an immunomodulatory potential that influences host defense and inflammation ( Paudel et al, 2017 ). Our results suggest that it is possible that the OMVs of A. paragallinarum involved in such influence on host responses.…”
Section: Discussionmentioning
confidence: 99%
“…In the lungs, bronchial goblet cell hyperplasia and hyperplasia of the bronchial lymphoid nodules were reported (Zepeda et al 2010). In another experimental G. anatis or G. anatis -A. paragallinarum co-infection study in chickens, histopathological findings in the infraorbital sinus and nasal turbinates observed were infiltration of inflammatory cells, predominated by mononuclear cells and heterophils, increased mucosal thickness, and necrosis and sloughing of epithelium (Paudel, Ruhnau, et al 2017). Few other similar recent experimental G. anatis infections in commercial broiler chickens reported the enhanced activity of goblet cells, hyperplasia of the epithelial lining, and inflammatory cell infiltration in tracheal tissue.…”
Section: Respiratory Organsmentioning
confidence: 96%
“…Flocks co-infected with other bacterial or viral infections and immunosuppressive agents should be protected by adopting appropriate prophylactic, therapeutic and control measures such as timely vaccination, selective antimicrobial therapy and strict biosecurity measures (He-Ping et al 2012;;Paudel et al 2015;Mataried 2016;Paudel, Ruhnau, et al 2017;El-Hamid et al 2018). Any stress that reduces bird resistance to infection must be ameliorated.…”
Section: Therapy and Prophylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…Gallibacterium anatis has emerged in the last few years as an important multi-antibiotic resistant pathogen in intensively reared poultry birds causing losses in production. It causes heavy mortality in broiler chickens and a drop in egg production in layer hens by triggering salpingitis, peritonitis, salpingoperitonitis, bacteremia, oophoritis, follicle degeneration, hepatitis, enteritis, and respiratory tract diseases [111][112][113][114]. G. anatis secretes a strongly cytotoxic and hemolytic RTX toxin named GtxA, which has a particularly high molecular mass of 215 kDa and an uncommon domain structure [115].…”
Section: Gtxa Martx From the Poultry Pathogen Gallibacterium Anatismentioning
confidence: 99%